2018
DOI: 10.1096/fj.201700895r
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells promote endothelial progenitor cell migration, vascularization, and bone repair in tissue‐engineered constructs via activating CXCR2‐Src‐PKL/Vav2‐Rac1

Abstract: Tissue-engineered constructs (TECs) hold great promise for treating large bone defects. Incorporated mesenchymal stem cells (MSCs) can facilitate the vascularization of TECs. Nevertheless, the underlying mechanism remains ambiguous. Here we analyzed the roles of C-X-C chemokine receptor 2 (CXCR2) and its downstream signal pathways in MSC-induced endothelial progenitor cell (EPC) migration. Transwell assays and immunofluorescence staining were performed for cell migration analysis in vitro and in vivo, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 57 publications
2
32
0
Order By: Relevance
“…As with bone defect modeling, we previously established a reliable and reproducible load-bearing, critical-size femoral defect model in mice with the help of a self-designed screw-plate fixation system. This model was successfully applied in basic research in the field of bone tissue engineering [16, 17]. In summary, the main research purpose, that is, to identify the origin of host cells involved in TEC-mediated bone repair, cannot be achieved in the absence of either model of GFP-BMT, parabiosis, or LSBD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As with bone defect modeling, we previously established a reliable and reproducible load-bearing, critical-size femoral defect model in mice with the help of a self-designed screw-plate fixation system. This model was successfully applied in basic research in the field of bone tissue engineering [16, 17]. In summary, the main research purpose, that is, to identify the origin of host cells involved in TEC-mediated bone repair, cannot be achieved in the absence of either model of GFP-BMT, parabiosis, or LSBD.…”
Section: Discussionmentioning
confidence: 99%
“…Decalcified bone matrix (DBM) scaffolds were chosen as cell carriers due to their excellent capacities of supporting the adhesion, growth, and proliferation of MSCs [16]. They were prepared using porcine trabecular bones from Yunnan miniature pigs according to a previously described method [17]. TECs were fabricated by dropwise instilling an aliquot (20 μ l, 1 × 10 6 cells/ml) of a single mBMSC suspension onto the two opposite surfaces of DBM.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we found that paracrine CXCL8 derived from BM‐MSCs also promoted AML cell proliferation and survival. CXCL8 exerts its effects on the target cells after binding to the CXCR2 receptor expressed on those cells; therefore, blocking the CXCL8–CXCR2 axis is of therapeutic potential in various solid tumors (20,30,39,43). Consistent with this, Schinke et al .…”
Section: Discussionmentioning
confidence: 99%
“…Active Rac1 and Cdc42 can then stimulate actin polymerization by activating actin nucleation-promoting factors like WAVE or N-WASP or activating PAK to activate ERK and cortactin. GIT2 was also reported to promote endothelial cell migration in response to CXCR2 by function with another Rac GEF, Vav2 [101]. Mechanistically, GIT2 appeared to stimulate Vav2, leading to Rac activation and increased migration induced by CXCR2.…”
Section: Arf Gaps In Motility-related Structures: Lamellipodia Stmentioning
confidence: 99%